Estimation of surface pressure distribution on a delta wing with curved leading edges in hypersonic/supersonic flow - Crasta, Asha; Pavithra, S; Khan, Sher Afghan (NOVA Science Publishers, 2016)
In this paper the focus is on study of surface pressure distribution variation with angle of incidence and Mach number for hypersonic flow/Supersonic flow for a delta wing with leading edges which are curved. It is found that the surface pressure on the wing increases with increase in incidence angle and the inertia level. Results are compared for M = 8.7, 10, and 17 for delta wing with leading edge straight and curved and the results are found to be in good agreement with existing theories.